Utilizando o software PictoBlox para o ensino de circuitos elétricos: uma abordagem prática no ensino médio - Alencar, Renan de Melo (2025)
This work aims to investigate and explore an additional method for teaching physics, using technology through robotics to teach concepts and practices related to electrical circuits. The goal is to examine the potential of using the Pictoblox platform as a supporting tool in high school physics education. Given the challenges faced in the learning process of this subject, often characterized by abstract and decontextualized approaches, this study seeks to assess how the introduction of a block-based programming language, integrated with sensors and electronic components, can contribute to building physics knowledge in a more interactive, experimental, and meaningful way. Thinking about overcoming such obstacles and motivating high school students to study physics, we thought of using the software PictoBblox, a tool based on SCRATCH, which allows the development of programming in blocks, and also allows connection to boards (microcontrollers) Arduino. The use of the Arduino board will be of great importance in this research, as this is the time when students will need to exercise their knowledge about circuits and, by building and handling variations of these circuits, it will be possible to achieve significant learning on the topic covered. The option to promote a didactic sequence using this software to teach electrical circuits is based on the use of technology to make physics more attractive and understandable to students, making them not only understand the content, but also recognize the importance of learning it.